Graphic memory and stylistic movements: initial typographic study of frontages and buildings in the historic center of Manaus (Revista de Ensino em Artes, Moda e Design, 2025)
In order to preserve the graphic memory of Manaus, an exploratory study was carried out on the influence of stylistic movements such as Art Nouveau, Art Deco and Beaux-Arts in the context of the Belle Époque and the beginning of Modernism, in the typographic artifacts found on the facades of buildings in the historic center of the city of Manaus. Photographic records obtained through a drift, according to the methodology adapted from Castelucci and Farias (2024), were analyzed using the visual content analysis approach of Gillian Rose (2016). The analysis revealed stylistic characteristics of these movements present in typographic specimens in the historic center of Manaus, highlighting the importance of preserving and documenting these elements. The study seeks to contribute to the recording of the graphic memory of Manaus and encourage the use of this data in the teaching of typography and in the appreciation of it as a historical and cultural heritage.
Keywords: Graphic memory; Historical center of Manaus; Stylistic movements; Typography; Teaching in Graphic Design